Distortions in economic evaluation promoted by cost accounting processing of interest-bearing liabilities in Brazil - Silva, Adail Marcos Lima da (Revista Gestão da Produção Operações e Sistemas, 2012)
This paper aims at exposing the distortions in the economic evaluation caused by calculating the cost of bank debt for financial statements – the ratio involving the financial expense and the value of liabilities acquired from the financial market. For the methodology, about the purposes, it can be considered explanatory, about the media, the literature. Based on the concept of total cost-effective released by the Central Bank of Brazil, the processing cost of the debt by the financial statements discloses inaccurate percentage, reflecting on the development of distorted economic evaluations. Indeed, the disharmony in discussion affects the fundamental analysis, widely used by investors and professionals in the financial market – in investment and financing decisions. Based on what was exposed, the achievement of a virtuous economic evaluation of financial statements should be understood as being some way off, being fulfilled only when the adoption of an accounting procedure can measure the cost of bank debt as it was held by the Central Bank of Brazil. Keywords: Cost of Bank Debt, Accounting Processing; Distortions in Economic Evaluation.